Combined DNA damage repair interference and ion beam therapy: development, benchmark, and clinical implications of a mechanistic biological model - Liew, Hans; Meister, Sarah; Mein, Stewart; Tessonnier, Thomas; Kopp, Benedikt; Held, Thomas; Haberer, Thomas; Abdollahi, Amir; Debus, Jürgen; Dokić, Ivana; Mairani, Andrea (International journal of radiation oncology, biology, physics, 2022)
Purpose - Our purpose was to develop a mechanistic model that describes and predicts radiation response after combined DNA damage repair interference (DDRi) and particle radiation therapy. - Methods and Materials - The heterogeneous dose distributions of protons and 4He ions were implemented into the “UNIfied and VERSatile bio-response Engine” (UNIVERSE). Predictions for monoenergetic and mixed fields over clinically relevant dose and linear energy transfer range were compared with experimental in vitro survival data measured in this work as well as data available in the literature, including different cell lines and DDR interferences. Ultimately, UNIVERSE predictions were investigated in a patient plan. - Results - UNIVERSE accurately predicts survival of cell lines with and without DDRi in clinical settings of ion beam therapy based only on 3 parameters derived from photon data. With increasing dose or linear energy transfer, the radiosensitizing effect of DDRi decreases, resulting in diminished relative biological effect of ion beam radiation for cells subjected to DDRi in comparison to cells that are not. Similar trends were observed in patient plan recalculations; however, this analysis also suggests that DDRi + particle radiation therapy may better preserve the therapeutic window in comparison to DDRi + photon radiation therapy. - Conclusions - The presented framework represents the first mechanistic model of combined DDRi and particle radiation therapy comprehensively benchmarked in clinically relevant scenarios and a step toward more personalized treatment. It reveals potential differences between DDRi + photon radiation therapy versus DDRi + particle radiation therapy, which have not been described so far. UNIVERSE could aid in appraising the clinical viability of combined administration of radiosensitizing drugs and charged particle therapy, as well as the identification of patients with known DDR deficiencies in the tumor who might benefit from therapy with light ions, freeing limited space at heavy ion therapy centers.